2017
DOI: 10.1111/eea.12624
|View full text |Cite
|
Sign up to set email alerts
|

Phengaris (Maculinea) teleius butterflies select host plants close to Myrmica ants for oviposition, but Pnausithous do not

Abstract: Many lycaenid butterfly species have interactions with ants, with 12% obligatorily depending on two sequential sources of larval food, namely host plants and host ants. When host plants are abundant but the density of host ant nests is relatively low, most host plants have no host ant nest in their vicinity and are thus unsuitable for larval survival. Obligatorily myrmecophilous female butterflies, whose caterpillars feed on ant larvae, would have a comparative advantage if they deposit eggs on host plants in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
0
6
0
3
Order By: Relevance
“…Spatial overlap between the distribution of host plants and host ant nests at larger scales has previously been shown to increase the density and population persistence of the congeneric species P. arion (Casacci et al., ; Thomas, Simcox, & Clarke, ). Other studies with Phengaris butterflies have demonstrated effects of host plant phenology (Thomas & Elmes, ; Valdés & Ehrlén, , ), Myrmica presence (Van Dyck et al., ; Wynhoff & van Langevelde, ; Wynhoff et al., ) or both of these factors (Casacci et al., ) for oviposition site selection. Our study suggests that the spatial overlap between these two resources also at the scale of the host plant individual is associated with butterfly oviposition preference, and that the effects of plant phenology and ant abundance are interactive.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Spatial overlap between the distribution of host plants and host ant nests at larger scales has previously been shown to increase the density and population persistence of the congeneric species P. arion (Casacci et al., ; Thomas, Simcox, & Clarke, ). Other studies with Phengaris butterflies have demonstrated effects of host plant phenology (Thomas & Elmes, ; Valdés & Ehrlén, , ), Myrmica presence (Van Dyck et al., ; Wynhoff & van Langevelde, ; Wynhoff et al., ) or both of these factors (Casacci et al., ) for oviposition site selection. Our study suggests that the spatial overlap between these two resources also at the scale of the host plant individual is associated with butterfly oviposition preference, and that the effects of plant phenology and ant abundance are interactive.…”
Section: Discussionmentioning
confidence: 97%
“…Previous observational studies have suggested that oviposition is host species dependent (Van Dyck et al., ). Experimental studies have found Phengaris oviposition to be dependent on Myrmica ant presence, but found no effect of species identity (Patricelli et al., ; Wynhoff & van Langevelde, ). Lastly, there are several studies that have found no evidence of ant‐dependent oviposition (Fürst & Nash, ; Nowicki, Witek, Skorka, & Woyciechowski, ; Thomas & Elmes, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations